The Role of Financial Literacy, Ease, and Trust in the Intentions of Students in Cirebon in Using Digital Finance - Eja Agustiana; Aprizal Suwanda; Putri Puspita Ayu (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study examines whether financial literacy, perceived ease, and trust can influence the increase in students' intention to use digital financial services. This research uses a quantitative approach processed using SPSS, with a sampling method through the Google Form platform and shared via social media. The population targeted by this study was students of the Faculty of Economics and Business, Swadaya Gunung Jati University, Cirebon. The sampling technique used was purposive sampling with certain predetermined criteria, with a sample of 258 respondents. The results showed that financial literacy, ease, and trust have a significant influence on the intention to use digital financial services. In particular, financial literacy has a positive impact, indicating that better financial understanding correlates with a higher propensity to adopt digital financial services. Nonetheless, these findings also highlight the need for increased financial literacy education, especially among university students.